Investigation of the interlayer and optical spacer effects in organic tandem solar cells - Firdaus Suhaimi (2010)
Organic tandem solar cells based on the solution processed bulk heterojunction blend of P3HT:PCBM as a photoactive layers have been successfully fabricated. In the first part of the project, a focus was placed on the interlayer structure (Au versus Al/Au) and its role as a charge recombination centre in the tandem cells. As the subcells are electronically coupled in series, the open-circuit voltage (Voc) of tandem cell is in principle the sum of the Voc of individual cells. In order to evaluate the contribution from subcells, the bottom and top reference cells were also modeled. The Al/Au interlayer facilitated a higher Voc in the tandem cell because Al in the interlayer system provides symmetry breaking and induces higher voltage across bottom cell. Tandem cell with Al/Au layer outperformed the single reference cells in Voc (1.05V to 0.67V and 0.63V) but it did not meet theoretical expectations (1.3V) due to incomplete ohmic contact at the interlayer interfaces. In addition, the short-circuit current Jsc and fill factor are lower in tandem cell. It would be attributed to an uneven light distribution between subcells and high series resistance of the device respectively. The high series resistance is supposed to be due to some bottleneck of the photo-induced carrier flow in the tandem structure.